(untitled) (Research, Society and Development, 2020)
Objective: To verify the impact of food on sleep habits. Methodology: The search for articles was carried out in the databases Scielo, Lilacs, MEDLINE (Pubmed), Scopus, Bireme and Web Of Science, there was no restriction on location, period and language. For the selection of studies, the combination based on the Medical Subject Heading Terms (MeSH) was used. Quality studies were included, with scores ≥ 6 points according to the qualitative score protocol proposed by Pithon et al. (2015). Results: Positive associations were found between average sleep duration and caloric and macronutrient intake per kilogram. Conclusion: Individuals who report "short" sleep durations are less likely to have a healthy diet and those who report "good" sleep quality are more likely to have a healthy diet. Adequate energy intake and a high quality diet can result in high quality sleep.